2007
DOI: 10.1111/j.1447-0756.2007.00543.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolated adenomyotic cyst associated with severe dysmenorrhea

Abstract: A case of a 23-year-old, nulliparous female with a very rare isolated adenomyotic cyst inducing severe dysmenorrhea was seen. Transvaginal ultrasonographic tomography and magnetic resonance imaging (MRI) showed a 3 x 3-cm cystic mass within the left anterior wall of the uterine corpus. The cystic space was filled with hyperintense fluid on T1-weighted images, which was surrounded by hypointense tissue beside the right uterine corpus on T2-weighted images. The case was preliminarily diagnosed using MRI as havin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 10 publications
1
40
0
Order By: Relevance
“…Several terms have been used to define these large cysts including adenomyotic cyst [6][7][8], cystic adenomyoma [9][10][11], and cystic adenomyosis [12,13]. According to Takeuchi et al [14], adenomyoma is a neoplastic tumor classified as a benign mixed epithelial-nonepithelial tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Several terms have been used to define these large cysts including adenomyotic cyst [6][7][8], cystic adenomyoma [9][10][11], and cystic adenomyosis [12,13]. According to Takeuchi et al [14], adenomyoma is a neoplastic tumor classified as a benign mixed epithelial-nonepithelial tumor.…”
Section: Discussionmentioning
confidence: 99%
“…But after operating, they found a hemorrhagic adenomyosis cyst measuring 3 cm within the left anterior wall of uterine corpus. 2 Ho ML et al also reported a similar case where ultrasonography demonstrated a large cystic lesion, which was localised to the myometrium on CT scan and MRI; the lesion was diagnosed to be cystic adenomyosis by pathology after surgical resection.…”
Section: Resultsmentioning
confidence: 91%
“…Adenomyotic cysts are usually observed in parous women, and usually seen in association with diffuse adenomyosis uteri [3]. But isolated adenomyotic cysts may also be detected [4,5]. Adenomyotic cysts are usually seen in older ages but they may be even detected in adolescents [5].…”
Section: Discussionmentioning
confidence: 99%
“…But even urinary retension may be the symptom of an adenomyomatous polyp [8]. Pain or severe dysmenorrhea may also be the main symptom in adenomyotic cysts [2,4,5]. This patient had also pelvic pain as the main symptom accompanied by dysmenorrhea and postcoital pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation